Verbal memory declines more in female patients with Parkinson's disease: the importance of gender-corrected normative data. Issue 11 (19th May 2016) - Fengler, S.; Roeske, S.; Heber, I.; Reetz, K.; Schulz, J. B.; Riedel, O.; Wittchen, H.U.; Storch, A.; Linse, K.; Baudrexel, S.; Hilker, R.; Mollenhauer, B.; et al.
Abstract : Background: Data on gender-specific profiles of cognitive functions in patients with Parkinson's disease (PD) are rare and inconsistent, and possible disease-confounding factors have been insufficiently considered. Method: The LANDSCAPE study on cognition in PD enrolled 656 PD patients (267 without cognitive impairment, 66% male; 292 with mild cognitive impairment, 69% male; 97 with PD dementia, 69% male). Raw values and age-, education-, and gender-corrected Z scores of a neuropsychological test battery (CERAD-Plus) were compared between genders. Motor symptoms, disease duration, l- dopa equivalent daily dose, depression - and additionally age and education for the raw value analysis - were taken as covariates. Results: Raw-score analysis replicated results of previous studies in that female PD patients were superior in verbal memory (word list learning, p = 0.02; recall, p = 0.03), while men outperformed women in visuoconstruction ( p = 0.002) and figural memory ( p = 0.005). In contrast, gender-corrected Z scores showed that men were superior in verbal memory (word list learning, p = 0.02; recall, p = 0.02; recognition, p = 0.04), while no difference was found for visuospatial tests. This picture could be observed both in the overall analysis of PD patients as well as in a differentiated group analysis. Conclusions: Normative data corrected for gender and other sociodemographic variables are relevant, since they may elucidate a markedly different cognitive profile compared to raw scores. Our study also suggests that verbal memory decline is stronger in women than in men with PD. Future studies are needed to replicate these findings, examine the progression of gender-specific cognitive decline in PD and define different underlying mechanisms of this dysfunction.